2020
DOI: 10.1002/app.49617
|View full text |Cite
|
Sign up to set email alerts
|

Poly(lactic acid)/pulp fiber composites: The effect of fiber surface modification and hydrothermal aging on viscoelastic and strength properties

Abstract: Poly(lactic acid) (PLA)/kraft pulp fiber (30 wt%) composites were prepared with and without a coupling agent (epoxidized linseed oil, ELO, 1.5 wt%) by injection molding. The non‐annealed composite samples, along with lean PLA, were exposed to two hydro‐thermal conditions: cyclic 50% RH/90% RH at 23 and 50°C, both up to 42 days. The aging effects were observed by size exclusion chromatography, differential scanning calorimetry, dynamic and tensile mechanical analysis, and fracture surface imaging. ELO temporari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…That points out that besides acting as a plasticizer, ELO can enhance even further the interaction between the matrix and the fibers. Despite some authors reporting that no major differences could be observed on the SEM micrographs upon incorporation of ELO in green composites of PLA reinforced with birch kraft pulp fibers [33,48], which was attributed to the reasonable interfacial adhesion already observed on the composites without the additive, some other studies revealed similar results to the ones obtained in the present work. For instance, composites of PLA with hazelnut shell flour (HSF) containing 7.5 wt.% ELO showed remarkably different fracture micrographs revealing improved interfacial adhesion [49].…”
Section: Morphological Characterizationsupporting
confidence: 76%
“…That points out that besides acting as a plasticizer, ELO can enhance even further the interaction between the matrix and the fibers. Despite some authors reporting that no major differences could be observed on the SEM micrographs upon incorporation of ELO in green composites of PLA reinforced with birch kraft pulp fibers [33,48], which was attributed to the reasonable interfacial adhesion already observed on the composites without the additive, some other studies revealed similar results to the ones obtained in the present work. For instance, composites of PLA with hazelnut shell flour (HSF) containing 7.5 wt.% ELO showed remarkably different fracture micrographs revealing improved interfacial adhesion [49].…”
Section: Morphological Characterizationsupporting
confidence: 76%
“…For instance, after the addition of 10 and 20 wt% of untreated CMF, the Tg of PLA was reduced to 57.7 °C and 56.1 °C, respectively. It can be assumed that the presence of moisture in fibers leads to the degradation of PLA chains, resulting in the lower values of Tg (Paunonen et al 2020).…”
Section: Characterization Of Pla-based Biocompositesmentioning
confidence: 99%
“…21 Due to the recognition of the issues of natural and synthetic ACEM materials, a series of strategies had been proposed to enhance their surface functional properties. [22][23][24] Hongsriphan and Sanga 25 applied chitosan solutions with different concentrations (0.25, 0.50, 1.00, and 2.00% w/v) to deposit an antibacterial layer on the surface of PLA; the results showed that the chitosan coating had enhanced the water vapor transmission rate, mechanical properties, and antibacterial activity against Staphylococcus aureus and Escherichia coli. Stoleru et al 26 adopted cold radiofrequency plasma in a nitrogen atmosphere to first activate surface active sites of PLA, and then to graft chitosan molecular via carbodiimide chemistry, achieving stable antibacterial activity, surface performance and wet hydrophilicity properties.…”
Section: Introductionmentioning
confidence: 99%